The German skill formation model in transition: from dual system of VET to higher education? - Martin Baethge; Andrä Wolter (Journal for Labour Market Research, 2015)
The German system of skill formation, in particular the dual system of vocational education and training (VET), is considered in the political economic debate to be a pillar of the German model, mainly for two reasons: On the one hand, training of skilled workers was supported by the specific path of development of diversified quality production from its beginning. On the other hand, the dual VET system represents one of the most important fields for the German corporatist governance system. The article develops the following ideas: the conditions of the German VET system fundamentally changed during the second half of the twentieth century: Cognitive preconditions for VET continuously increased, and since the mid-1960s educational reform and expansion in Germany (old Länder) gradually resulted in increasing higher levels of education and in a differentiation of the educational landscape as well as in a shift in young peoples' educational careers towards higher education. The driving forces behind these developments will be analysed and discussed with respect to their impact on the relation between the dual VET system and higher education. The argumentation results in the following conclusion: Firstly, the broad trend toward upskilling the German labour force will continue and the integration of low-qualified youth into VET and the labour market will become more precarious than in the past. Secondly, corporatist governance of the dual VET-System will come more and more under pressure and become less important in the German educational system as a whole.
Keywords: 330; Berufsbildungssystem - historische Entwicklung; duales System; Berufsausbildung; Hochschulbildung; Beschäftigungsentwicklung; Qualifikationsanforderungen; Fachkräftebedarf; Governance; Akademisierung